Cloning and Characterization of the pnb Genes, Encoding Enzymes for 4-Nitrobenzoate Catabolism in Pseudomonas putida TW3 - Hughes, Michelle A. (American Society for Microbiology, 2001)
Pseudomonas putida strain TW3 is able to metabolize 4-nitrotoluene via 4-nitrobenzoate (4NBen) and 3, 4-dihydroxybenzoic acid (protocatechuate [PCA]) to central metabolites. We have cloned, sequenced, and characterized a 6-kbp fragment of TW3 DNA which contains five genes, two of which encode the enzymes involved in the catabolism of 4NBen to PCA. In order, they encode a 4NBen reductase (PnbA) which is responsible for catalyzing the direct reduction of 4NBen to 4-hydroxylaminobenzoate with the oxidation of 2 mol of NADH per mol of 4NBen, a reductase-like enzyme (Orf1) which appears to have no function in the pathway, a regulator protein (PnbR) of the LysR family, a 4-hydroxylaminobenzoate lyase (PnbB) which catalyzes the conversion of 4-hydroxylaminobenzoate to PCA and ammonium, and a second lyase-like enzyme (Orf2) which is closely associated with pnbB but appears to have no function in the pathway. The central pnbR gene is transcribed in the opposite direction to the other four genes. These genes complete the characterization of the whole pathway of 4-nitrotoluene catabolism to the ring cleavage substrate PCA in P. putida strain TW3.